From Broken Windows to Perceived Routine Activities: Examining Impacts of Environmental Interventions on Perceived Safety of Urban Alleys - Jiang, Bin; Mak, Cecilia Nga Sze; Zhong, Hua; Larsen, Linda; Webster, Christopher John (Frontiers in Psychology, 2018)
In high-density cities around the world, alleys are common but neglected spaces that are perceived as unsafe. While cities have invested resources in environmental interventions to improve safety in urban allies, it is not clear how these interventions impact perceived safety. We review two important criminology theories that discuss the environmental and social factors that lead to crime: the Broken Windows Theory and the Routine Activity Theory. We argue that these theories can also be used to explain safety perceptions of urban environments, and then develop urban alley interventions based on these theories. We test people’s perceived safety of these interventions through a photograph survey. Results show that all interventions yielded higher perceived safety than existing alley scenes. Interventions based on the Broken Windows Theory (cleaning or vegetation interventions) yielded only modest improvements in perceived safety, while interventions based on the Routine Activity Theory (urban function interventions) yielded higher ratings. Our findings question the dominant use of the Broken Windows Theory in environmental interventions to promote perceived safety and argue for a more effective approach: urban function interventions inspired by the Routine Activity Theory.